Strategi Pengembangan Wisata Sejarah Di Daya Tarik Wisata Candi Sumberawan, Kabupaten Malang, Jawa Timur - Handayani, Tikasari; Suryasih, Ida Ayu; Sunarta, I Nyoman (JURNAL DESTINASI PARIWISATA, 2024)
Tourism with historical aspects offers significant opportunities to attract the attention of tourists due to the diversity of stories and backgrounds associated with each historical relic across different regions in Indonesia. One such example is the Sumberawan Temple, a historical tourism attraction in Malang Regency. The uniqueness of Sumberawan Temple as the only Buddhist stupa in East Java Province creates its own allure. This research aims to analyze strategies that can be implemented to develop the historical tourism appeal of Sumberawan Temple in Malang Regency, East Java. This study utilizes a combination of qualitative and quantitative data, with data sources from both primary and secondary sources. Data collection methods include interviews, observations, literature reviews, and documentation. The research findings indicate that attractions such as the beauty of the stupa, traditional ceremonies, photography opportunities with historical objects, and spring rituals enhance the historical appeal of the temple. Adequate facilities, accessibility, and active involvement of the local community in management enrich tourists' experiences. Information provided by the information center supports tourists' understanding of the temple's history. The Development Strategy for the Historical Tourism Appeal of Sumberawan Temple employs a SWOT (Strengths, Weaknesses, Opportunities, Threats) approach to formulate robust strategies. These include promotion through narrative storytelling or storynomics, the development of a local cultural events calendar, strengthening local cuisine, involving community participation in facility improvements, training, and crowdfunding, developing integrated tour packages, historical tourism guide education, improving public transportation, and cultural preservation programs. Keywords: Development Strategy, Historical Tourism, Sumberawan Temple